2019
DOI: 10.1007/s00127-019-01667-0
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric comorbidity as a risk factor for the mortality of people with bulimia nervosa

Abstract: Background Bulimia nervosa (BN) is associated with increased mortality. Frequent comorbidities of BN include substance use disorders, affective disorders and personality disorders (PD). These comorbidities may add an additional risk for mortality. Methods We investigated the influence of these psychiatric comorbidities on all-cause mortality with demographic and socioeconomic factors considered as confounders over an observation period from people with BN using anonymised health records data from the South Lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 69 publications
2
21
0
Order By: Relevance
“…Rates were higher for males [SMR 7.2 (95% CI 6.6–8.0)] compared to females [SMR 4.6 (95% CI 4.3–4.9)]. This is in line with other recent studies that also found higher mortality rates among males: in people treated for bulimia nervosa in secondary mental healthcare services an overall SMR of 2.5 (95% CI 1.5–4.0) was reported, with significantly higher rates among males compared to females [crude hazard ratio 5.4 (95% CI 1.8–16.5)] [ 54 ]. In another study on hospitalization for anorexia nervosa, in-hospital mortality in males was more than twice that for females [odds ratio 2.4 (95% CI 1.5–3.8)] [ 55 ].…”
Section: Incidencesupporting
confidence: 89%
“…Rates were higher for males [SMR 7.2 (95% CI 6.6–8.0)] compared to females [SMR 4.6 (95% CI 4.3–4.9)]. This is in line with other recent studies that also found higher mortality rates among males: in people treated for bulimia nervosa in secondary mental healthcare services an overall SMR of 2.5 (95% CI 1.5–4.0) was reported, with significantly higher rates among males compared to females [crude hazard ratio 5.4 (95% CI 1.8–16.5)] [ 54 ]. In another study on hospitalization for anorexia nervosa, in-hospital mortality in males was more than twice that for females [odds ratio 2.4 (95% CI 1.5–3.8)] [ 55 ].…”
Section: Incidencesupporting
confidence: 89%
“…The comorbidity exposures of interest were diagnoses of substance misuse (F10–F19), bipolar disorder (F31), depression (F32 and F33), and personality disorder (F60) determined by structured information in EHRs on diagnoses from drop‐down fields in the source record. The selection of comorbid diagnoses was based on previous studies using similar data sources, which were known to be most associated with this study's primary outcome of interest (Himmerich et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Eating disorders (ED) include a variety of diagnoses such as anorexia nervosa (AN), bulimia nervosa (BN), and eating disorder otherwise not specified (EDNOS) (American Psychiatrist Association [APA], ). ED patients have high rates of mortality with psychiatric comorbidity contributing to these elevated rates (Himmerich et al , Himmerich et al ). They are more likely to present to hospital with self‐harm (Perez, Marco, & Canabate, ; Smithuis et al, ) or a suicide attempt (Suokas et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…10 More than 70% of people with eating disorders report concomitant psychiatric comorbidity-affective disorders, anxiety, substance use, and personality disorders are most common in BN. 11 Psychiatric comorbidities as well as hopelessness, shame, and impulsivity associated with the illness may contribute to challenges with nonsuicidal self-harm, suicidal ideation, and death by suicide. Individuals with BN experience lifetime rates of nonsuicidal self-harm of 33% and are nearly 8 times more likely to die by suicide than the general population.…”
Section: ■ Onset In Adolescence and Fairly Commonmentioning
confidence: 99%